285 Effect of low Protein Diets on Oxidative Stress, Plasma Metabolomics and Cecal Microbiome of Broiler Chickens During Experimentally Induced Heat Stress. (21st September 2022) - Sutton, Julia; Habibi, Mohammad; Shili, Cedrick n; Pezeshki, Adel
Abstract: Low-protein diets mitigate the negative outcome of heat stress in birds; however, the underlying mechanisms are largely unknown. The objective of this study was to investigate the effects of low-protein diets on broilers oxidative stress, plasma metabolomics and cecal microbiota composition during experimentally induced heat stress. Two-hundred-day-old male broiler chicks were assigned into 36 pens with of 5-6 chicks/pen. All pens were weight-matched and randomly subjected into either thermoneutral (TN) or heat stress (HS) with 18 pens/treatment. Within each treatment, the birds were randomized to receive either normal protein (NP) or low protein (LP) diets with 9 pens/diet (50 birds/diet). The study lasted 6 weeks with 2 weeks of acclimation (starter phase) and 4 weeks of data collection (grower and finisher phases). On week 6, birds were euthanized and blood and cecal samples were collected. Oxidative stress biomarkers and peak height of metabolites in plasma were analyzed using GLM procedure (SPSS). Paired t-test was used for comparing diet treatments within TN and HS groups. Under TN condition, birds fed with LP had a decreased plasma superoxide dismutase activity and lipid peroxidation compared with NP (P< 0.05), but no differences on these measurements were detected during HS (P>0.05). Birds fed with LP diet had a greater lipid hydroperoxides than NP under HS (P< 0.05). Principal component analysis showed a clear separation for plasma metabolites found between NP and LP diets under TN and HS. Dietary protein content impacted plasma metabolites related with metabolism and biosynthesis of alanine, aspartate, glutamate and phenylalanine during both TN and HS. Compared with NP, cecal contents of chickens fed with LP diet had greater abundances of p_Tenericutes, c_Mollicutes, c_Mollicutes_RF9, and f_tachnospiraceae under HS. Thus, dietary protein content influenced the plasma metabolites with similar pattern during TN and HS, but that had differential effects on cecal microbiota composition under TN and H.